Karakteristik Campuran Laston BC Menggunakan Batu Sungai Cikkee Kecamatan Lalabata Kabupaten Soppeng - Maryadi Anan Lalembang; Alpius; Wona Grace Boro (Paulus Civil Engineering Journal, 2022)
Roads are economic supporting infrastructure that connects an area with other areas that are used by the general public and passed by various kinds of vehicles. With the increase in population, there is also an increase in the volume of vehicles and loads passing over the road pavement structure. The development of technology in the field of road traffic and pavement so that good aggregate quality is needed in a mixture of road pavement structures that have good durability and are not easily damaged. Therefore, it must be tested for aggregate characteristics, especially for Laston BC before use. This study was designed to test the characteristics of the BC concrete asphalt layer mixture with the use of Cikkee River stones, Lalabata District, Soppeng Regency with the use of variations in asphalt content of 0.50% addition, namely the range of 5% to 7% using the Conventional Marshall and Immersion tests. The test results showed that the value of the characteristics of the mixture using Cikee River stones in the form of stability, flow, VIM, VMA and VFB for conventional Marshall test results met the specifications. For the Marshall Immertion test, a residual Marshall Stability (SMS) value of 93.7% was obtained with the use of an optimum asphalt content of 6% meeting the specifications required by Bina Marga.